Essays in Hindu theology - Rambachan, Anantanand, 1951- (Fortress Press, 2019)
This work offers a series of theological explorations into questions of both contemporary and enduring interest in the Hindu tradition. These reflections build dialogical bridges with other religious traditions around matters of shared concern, including the nature of theology, vocation, social justice, nationalism, and violence and non-violence. In exploring these issues, Rambachan draws deeply from authoritative Hindu sources and offers an interpretation of the Hindu tradition to meet the challenges of the modern world.